2011
DOI: 10.1055/s-0031-1299998
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-term Application of Crataegus oxyacantha on Ischemia and Reperfusion Induced Arrhythmias in Rats

Abstract: The effect of long-term application of Crataegus oxyacantha on ischemia and reperfusion induced arrhythmias was investigated in Wistar rats on the heart in situ and on Langendorff preparations. Seventeen rats were fed for 8 weeks with 0.5 g/kg b.w. Crataegus extract per day, standardised to 2.2% flavonoids. Twenty age-matched untreated rats served as controls. In the hearts in situ as well as in the Langendorff preparations the left anterior descending coronary artery (LAD) was ligated for 20 min and subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Next, the multichannels and multifunctions increase the therapeutic management of AF but reduce the side effects and the amount of drugs that only target one principle. Moreover, since exercise capacity [ 23 ], physical rehabilitation [ 67 ], and some mental problems [ 77 ] can be improved by TCMs, especially the nondrug methods, patients' life quality can be markedly enhanced. Finally, as AF is age-related and the old person has low tolerance for drugs because of declined function of liver and kidney, TCMs which have low adverse reaction [ 43 , 53 ] will be a better choice for them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, the multichannels and multifunctions increase the therapeutic management of AF but reduce the side effects and the amount of drugs that only target one principle. Moreover, since exercise capacity [ 23 ], physical rehabilitation [ 67 ], and some mental problems [ 77 ] can be improved by TCMs, especially the nondrug methods, patients' life quality can be markedly enhanced. Finally, as AF is age-related and the old person has low tolerance for drugs because of declined function of liver and kidney, TCMs which have low adverse reaction [ 43 , 53 ] will be a better choice for them.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this theory, a research discovered that two proanthocyanidins of its flower heads, catechin and epicatechin, inhibited the biosynthesis of thromboxane A2, leading to antiplatelet effect, but may increase the risk of bleeding [ 12 ]. Currently, hawthorn is widely used in cardiovascular diseases, especially arrhythmia [ 22 ], congestive heart failure [ 23 – 26 ], and hypertension [ 27 ]. Studies demonstrated that the biochemical mechanism of antiventricular arrhythmia is prolonging the APD through blocking the delayed (IK) and inward (IK1) rectifier potassium currents [ 22 ].…”
Section: Single Chms or Bioactive Ingredientsmentioning
confidence: 99%
“… 19 According to electrophysiological studies done by Muller et al., the methanolic extract of Crataegus suppressed both the delayed and inward K+ rectifier currents in guinea-pig ventricular myocytes respectively by 25% and 15% but did not affect ICa-L. 20 Conversely, in another study, the pretreatment of rats with 1% Crataegus oxyacantha extract (8 weeks) had no anti-arrhythmic property during ischemia or reperfusion periods, neither in the isolated nor in situ hearts. 21 Furthermore, in a study on healthy volunteers, an orally single dose of 160 mg Crataegus oxyacantha made no changes in ECG parameters. 22 Some studies reported that Hawthorn can increase the activity of digitalis and hence its potential toxicity and pro-arrhythmic effect and it has been recommended precautions about using this plant with digitalis.…”
Section: Plants and Their Ingredients With Antiarhythmic Propertiesmentioning
confidence: 96%